Let's assume Felisa's current age is F and the judge's current age is J.
According to the first statement, we have:
F + J = 20
According to the second statement, one year from now Felisa's age will be F + 1 and the judge's age will be J - 1. And based on the information in the problem, we have:
F + 1 = 9(J - 1)
Now, we can solve these two equations simultaneously:
1. F + J = 20
2. F + 1 = 9J - 9
By substituting the second equation into the first equation, we get:
(9J - 9) + J = 20
10J - 9 = 20
10J = 29
J = 29/10
J = 2.9
Now, substitute J back into the first equation to solve for F:
F + 2.9 = 20
F = 20 - 2.9
F = 17.1
Therefore, Felisa is 17.1 years old and the judge is 2.9 years old.
9. The sum of Felisa's age and judge age is 20. Felisa's age one year from now will be nine times judges age one year ago. How old is each now?
1 answer